Environmental Care Character Building Strategy - Aldyan Ismail; Yanuar Luqman; Lilin Budiati (Indonesia Approach Education, 2023)
This study aims to evaluate the implementation of Environmental Education at State High School 1 Gondangwetan Pasuruan in line with the implementation of the independent curriculum. The method used is a qualitative descriptive method, where the researcher collected data through direct observation at the school and interviews with teachers and students as the sources of information. Data analysis was conducted using the Miles and Huberman approach, which involved data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that State High School 1 Gondangwetan Pasuruan is a school that has been recognized as an Independent Adiwiyata school by implementing environmental education effectively. The implementation of environmental education is carried out through the integration of the curriculum in various subjects, including Biology, Indonesian Language, English Language, Entrepreneurship, Arts, and Culture. Environmental-related materials have been incorporated into the teaching and learning process of these subjects with the aim of transforming students' mindset towards the environment. Furthermore, State High School 1 Gondangwetan Pasuruan also engages students in extracurricular and cultural activities that support environmental education. Some of the activities carried out include leaf composting, plastic waste management using the ecobrick method, and the establishment of a waste bank. Through these activities, students are actively involved in environmental conservation efforts and waste management. This study highlights the novelty of integrating environmental education within the independent curriculum implemented at State High School 1 Gondangwetan Pasuruan. It showcases the school's innovative approach to incorporating environmental-related materials into various subjects, fostering a comprehensive understanding of environmental issues among students.